2008
DOI: 10.1016/j.mce.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Hormone affinity and fibril formation of piscine transthyretin: The role of the N-terminal

Abstract: SummaryTransthyretin (TTR) transports thyroid hormones (THs), thyroxine (T 4 ) and triiodothyronine (T 3 ) in the blood of vertebrates. TH-binding sites are highly conserved in vertebrate TTR however, piscine TTR has a longer N-terminus which is thought to influence TH-binding affinity and may influence TTR stability. We produced recombinant wild-type sea bream TTR (sbTTRWT) plus two mutants in which six (sbTTRM6) and twelve (sbTTRM12) N-terminal residues were removed. Ligandbinding studies revealed similar af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Furthermore, depending on the conditions used, fibrils of different morphology were obtained. Recent studies have shown that sbTTR binds thioflavin-T (ThT) at low pH, suggestive of amyloid [33]. In our study, we verified that sbTTR forms fibrillar structures at low pH that are similar in shape to those of hTTR.…”
supporting
confidence: 84%
“…Furthermore, depending on the conditions used, fibrils of different morphology were obtained. Recent studies have shown that sbTTR binds thioflavin-T (ThT) at low pH, suggestive of amyloid [33]. In our study, we verified that sbTTR forms fibrillar structures at low pH that are similar in shape to those of hTTR.…”
supporting
confidence: 84%
“…In a previous study, comprising an analysis of chimeric TTRs that have had the N‐terminal sequence changed to that of a TTR of a different species, but which exist in nature, we demonstrated the involvement of the N‐terminal segment with respect to TTR in its binding with TH [29]. This involvement was subsequently confirmed using truncated TTRs [57]. However, only by shortening the amino acid sequence to an appropriate length could effect on the binding clearly be shown.…”
Section: Discussionmentioning
confidence: 55%
“…These data led to the postulation that the N‐terminal region has a role in determining the binding affinities of T3 and T4 for transthyretin. This hypothesis was subsequently supported by others using fish‐truncated transthyretin [55].…”
Section: Functions Of Transthyretinmentioning
confidence: 61%
“…During the evolution of vertebrates, the binding affinities of transthyretin to THs varied [8,16,37,39,55]. The binding to T4 increased, while the binding to T3 decreased, during the evolution of eutherians from their ancestors.…”
Section: Influence Of the N-terminal Structure On The Th Distributor mentioning
confidence: 99%